Teaching of bioethics in dental graduate programs in Brazil Ensino de bioética em programas de pós-graduação em Odontologia no Brasil - Carolina Patrícia Aires; Fernando Neves Hugo; Pedro Luiz Rosalen; Fernanda Klein Marcondes (Sociedade Brasileira de Pesquisa Odontológica, 2006)
In the field of human research, researchers are faced with unexpected moral dilemmas, as a result of the development of technologies applied to health. Due to the great importance of this issue, our objective was to evaluate bioethics instruction in the education of researchers in Brazilian graduate programs in dentistry. Eighty-seven graduate programs in dentistry, recognized by CAPES (Coordination for the Improvement of Higher Education Personnel) were evaluated in this study. Data were extracted independently by two researchers from the CAPES website, and from the websites of the graduate programs, directly or via links to the programs available at the CAPES website. Forty-eight out of 87 programs had an ethics/bioethics course as part of their curricula. Of the graduation programs graded 5, 6 or 7 by CAPES, 38% included bioethics courses, while 62% of the programs graded 3 or 4 by CAPES had bioethics courses as part of their curricula. These findings are an alert to those involved in dental research education, as they showed that, although resolution 196/96 by the National Council of Health regulating human research in Brazil was published ten years ago, bioethics instruction in Brazilian graduate programs in dentistry is still at an incipient stage. This situation indicates a need for ethics pedagogy in the education of young researchers. O desenvolvimento de tecnologias aplicadas à saúde traz dilemas morais inesperados aos profissionais de pesquisa, em relação às práticas que envolvem seres humanos. Devido à relevância deste assunto, o objetivo deste estudo foi avaliar o ensino de bioética na educação de estudantes de programas de pós-graduação em Odontologia do Brasil. Oitenta e sete programas de pós-graduação em Odontologia, avaliados pela CAPES (2001-2003), foram estudados. Os dados foram extraídos, de maneira independente, por 2 avaliadores, por meio de consulta ao sítio da CAPES e aos sítios eletrônicos dos programas, diretamente ou via links dos programas disponíveis no sítio da CAPES. Dos 87 programas, 48 apresentaram disciplina de Ética/Bioética. Trinta e oito porcento dos programas com conceitos 5, 6 e 7 da CAPES mantêm disciplinas de Bioética, enquanto 62% dos programas com conceitos 3 e 4 apresentaram conteúdos de Bioética. Desta forma, os resultados deste estudo representam um alerta para os educadores envolvidos em ensino da pesquisa odontológica. Estes resultados também mostraram que a instrução em bioética ainda é incipiente nos programas de pós-graduação em Odontologia no Brasil, ainda que a resolução 196/96 do Conselho Nacional de Saúde tenha sido publicada há dez anos. Por este motivo, seria necessário assegurar uma pedagogia ética na formação do jovem pesquisador.